The effect of intergenerational support from children on loneliness among older adults-the moderating effect of internet usage and intergenerational distance - Huang, Ruyi; Gong, Rengui; Deng, Qiong; Hu, Yangming (Frontiers in Public Health, 2024)
Objective: Loneliness is a key social and public health issue, mainly affecting the mental health of older adults. The article aimed to explore the influence of intergenerational support from children on loneliness among older adults. Meanwhile, the article also analyzed the moderating effects of internet usage and intergenerational distance in this process.Methods： Based on the data received from 2018 China Longitudinal Aging Social Survey (CLASS), the ordinary least square (OLS) regression model was used to analyze the influence of intergenerational support from children on loneliness among older adults. Furthermore, the Bootstrap method was used to test the moderating effect of internet usage and intergenerational distance on the relationship between intergenerational support from children on loneliness among older adults.Results: Baseline regression showed that economic support (β=-0.059, P<0.001), caregiving support (β=-0.070, P<0.001), and emotional support (β=-0.108, P<0.001) from children can positively influence loneliness among older adults. Meanwhile, the results of the moderated effects analysis showed that internet usage and intergenerational distance moderates the relationship between caregiving support, emotional support from children and loneliness among older adults.The article demonstrates that family support, particularly intergenerational support from children plays a pivotal role in alleviating loneliness among older adults, so the government should further regulate the behavior of children's alimony support, improve the digital infrastructure, these measures help to reduce loneliness among older adults and expand the depth and breadth of family eldercare.